Answer:
y - 2 = 6 (x - 1)
Explanation:
Slope intercept form equations look like this:
y - y1 = m (x - x1)
***m =
Using the point (1,2), we know that x1 = 1 and y1 = 2. Let's sub these values into the slope intercept equation:
y - 2 = m (x - 1)
To complete this equation, we need to find slope. Pick out another point on the graph and plug into the slope equation. We can use point (2,8), where (1,2) = Point 1 and (2,8) = Point 2.
Now that we know m = 6, let's plug that back into the original equation to get our final answer:
y - 2 = 6 (x - 1)
I hope this helps!